Interactive design and architecture by using virtual reality, augmented reality and 3D printing. (7th January 2021) - Gonzalez, Nora Argelia Aguilera; Suarez-Warden, Fernando; Milian, Hector Nahun Quintero; Hosseini, Samira
New methods of teaching architectural design consider the elements of religion, spirituality, modernism, history and other cultural factors to address the physical, spatial and emotional needs of society. This article presents an educational training that emphasises on these critical elements. This paper describes a basic design course taught to second-semester students in the design and architecture course using virtual reality (VR), augmented reality (AR), and 3D printing to incorporate inner sensations and feelings of a human being in the designs. Applied techniques have transformed the classrooms into interactive spaces where the professors use strategies requiring the participants to work together to achieve the objectives of the course. Acquiring skills to create two-dimensional (2D) and three-dimensional (3D) representations facilitated the final products that meet the needs of the users in multitude of manners. The results of this project demonstrated an increase in spatial visualisation, analysis, and critical thinking among the students. Additionally, 100% of the students showed high level of satisfaction with the course and the experience of using these technological tools in the design and architecture course.